Interaction analysis of sharia financial institution assets, sharia investment and exports on gross domestic product in Indonesia - Nasyaa, Sultan Rasy; Imsar, Imsar; Harahap, Muhammad Ikhsan (Journal of Islamic Economics Lariba, 2024)
IntroductionIn macroeconomics, one of the key indicators influencing a country's economic success is its economic growth. An essential factor in determining a nation's economic growth is the Gross Domestic Product (GDP).ObjectivesThis research aims to analyze the level of interaction between Islamic financial institutions, Sharia investments, and export activities in Indonesia, examining their impact on the Gross Domestic Product (GDP) over the short and long term, spanning the period 2017-2022.MethodThe study employs a quantitative research approach, specifically utilizing the Vector Error Correction Model (VECM) method.ResultsThe results of the Vector Error Correction Model (VECM) reveal two significant variables in the long term. The causality test results indicate a significant relationship between Indonesian exports and Sharia investment. The Variance Decomposition analysis reveals that Sharia Financial Institution Assets contribute 2.7 percent, followed by Sharia Investment at 0.3 percent, and Indonesian Exports at 0.03 percent to the variation in GDP.ImplicationsThis suggests that Indonesian exports significantly impact Sharia investment, and vice versa. However, concerning Gross Domestic Product (GDP), none of the variables exhibit significance. The development of income across various institutions and economic activities in Indonesia indicates a significant increase in the last three years.Originality/NoveltyThese findings provide valuable insights into the economic dynamics of Indonesia, offering a basis for further research and policymaking.